EVALUASI KUALITAS MARKETPLACE ABC.COM BERDASARKAN KERANGKA KERJA KEPUASAN PENGGUNA, WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Aditya Rachmadi; Admaja Dwi Herlambang; Nozomi Alifia Ghaisani (Universitas Islam Lamongan, 2018)
Competition between companies especially in e-commerce is increasingly fierce nowadays. ABC.com is a website that provides marketplace service, by providing better website it can improve service for their customer. This study aim to identify and prioritize factors that affect marketplace quality at ABC.com. The research approach used is quantitative approach with descriptive analysis. Sample selected from the population of user who have ABC.com account that amount to total 1.700..000 registered user Sampling method used is convenience sampling that provide 109 respondent. Data collection is done through a questionnaire and provide factors that affect marketplace namely usability, information quality, service interaction quality, and user satisfaction. These factors is in the high category especially in indicator transaction and information security that placed in the A quadrant. While other indicators like performance, timeliness, purchase satisfaction and experience satisfaction placed in low priority (C quadrant). Recommendation for this study are ABC.com should increase their transaction process, information security and performance to obtain customer satisfaction in purchase activities that drive experience satisfaction.